1985
DOI: 10.1016/0043-1648(85)90087-0
|View full text |Cite
|
Sign up to set email alerts
|

Steady motion of an insulating rigid flat-ended punch over a thermally conducting half-plane

Abstract: An insulated, rigid, flat-ended punch moving steadily over the surface of a half-plane is considered. It is assumed that the motion has been sustained for a sufficiently long period for a steady thermal state to have been achieved, the source of heat being the energy dissipated at the interface due to Coulomb friction. The effect of thermal distortion on the contact pressure dist~bution is found and the temperature profile under the punch is given. A closed-form solution is found for the case of large Peclet n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 2 publications
1
18
1
Order By: Relevance
“…It is to be remarked that for verification purposes, the work conducted by Guler [12], Hills and Barber [7] for isothermal contact of metal half-plane when sliding velocity V¼0.0 is one of the particular cases of the present thermoelastic contact problem. Moreover, for other cases, the results of present study are compared with works conducted by Hills and Barber [7] and Ke et al [25] In these studies, Hills and Barber [7] and Ke et al [25] take into account the convective effect due to the sliding of the punch. This effect can be defined by introducing the 'Pe' (Peclet) number for sliding contacts and this non-dimensional number sets a relationship between the sliding velocity of the punch and the thermal diffusivity of the contacting material.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is to be remarked that for verification purposes, the work conducted by Guler [12], Hills and Barber [7] for isothermal contact of metal half-plane when sliding velocity V¼0.0 is one of the particular cases of the present thermoelastic contact problem. Moreover, for other cases, the results of present study are compared with works conducted by Hills and Barber [7] and Ke et al [25] In these studies, Hills and Barber [7] and Ke et al [25] take into account the convective effect due to the sliding of the punch. This effect can be defined by introducing the 'Pe' (Peclet) number for sliding contacts and this non-dimensional number sets a relationship between the sliding velocity of the punch and the thermal diffusivity of the contacting material.…”
Section: Resultsmentioning
confidence: 97%
“…Barber and Moran [6] also used Green's functions to solve the unsteady thermoelastic contact problems, heat source was defined analytically on the contact zone and the analytic expressions on the contact zone was discretized to solve the problem numerically. Contact problem of sliding rigid insulated punch and a metallic substrate was investigated in the work conducted by Hills and Barber [7] and heat generation due to the Coulomb type friction was taken into account. The effects of thermal deformations on contact stresses were represented and significant results were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal energy leads to the gradual thermal deformation that interferes with the uniform contact between the disk and pads. Even worse than this, periodically distributed hot spots (causing hot roughness) have been frequently observed on the surfaces of disks during their operation (Barber, 1967;Hills and Barber, 1985). The hot roughness clearly induces non-smooth contact that is the origin of low frequency noise in brake systems.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the fact that the frictional heat flows only into the graded layer through the contact area without any loss to the surroundings [37], the problem is treated within the linear thermoelasticity framework. According to Joachim-Ajao and Barber [52], the heat flux generated by the tangential traction inside the contact area is modeled to equal the generating rate of frictional heat,…”
Section: Thermal Boundary Conditionsmentioning
confidence: 99%
“…Barber and his collaborators [36,37] have shown that, for a thermoelastic contact model, pronounced differences from an isothermal one can be found. Steady sliding of a conducting cylinder over an insulating half-plane always results in a narrower contact width comparing to the isothermal problem.…”
Section: Introductionmentioning
confidence: 99%